2021
DOI: 10.1007/s40333-021-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of cultivable endophytic bacteria associated with halophytes in Xinjiang of China and their plant beneficial traits

Abstract: Endophytic bacteria from halophytes have a wide range of application prospects in various fields, such as plant growth-promoting, biocontrol activity and stress resistance. The current study aimed to identify cultivable endophytic bacteria associated with halophytes grown in the salt-affected soil in Xinjiang Uygur Autonomous Region, China and to evaluate their plant beneficial traits and enzyme-producing activity. Endophytic bacteria were isolated from Reaumuria soongorica (PalL Maxim.), Artemisia carvifolia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…There are numerous reports and abundant evidence about improved growth, development, and stress tolerance of plants in natural environments or under induced salinity provided by halotolerant, plant-beneficial endophytic bacteria. Such bacteria, associated with Psoralea corylifolia [ 45 ] and Lycium ruthenicum [ 46 ], enhanced stress tolerance and the development of wheat. Halotolerant B. alcalophilus and B. thuringiensis isolated from Arthrocnemum macrostachyum (Moric.)…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports and abundant evidence about improved growth, development, and stress tolerance of plants in natural environments or under induced salinity provided by halotolerant, plant-beneficial endophytic bacteria. Such bacteria, associated with Psoralea corylifolia [ 45 ] and Lycium ruthenicum [ 46 ], enhanced stress tolerance and the development of wheat. Halotolerant B. alcalophilus and B. thuringiensis isolated from Arthrocnemum macrostachyum (Moric.)…”
Section: Discussionmentioning
confidence: 99%
“…have previously been isolated from tomato roots (Zhu et al, 2021), rice roots (Khaskheli et al, 2020;Shabanamol et al, 2021); and Peribacillus spp. was previously isolated from P. harmala (Li et al, 2021) and canola crop roots (Martínez-Hidalgo et al, 2021), making our study one of the few to isolate and report Peribacillus sp. as an endophyte.…”
Section: Discussionmentioning
confidence: 99%
“…Although five bacterial endophytes were isolated in this study, the data adds to the minimally reported phyllosphere bacterial endophytes ( Sivakumar et al, 2020 ). Li et al (2021) , reported a minimal number of bacterial endophytes from halophytes, with five bacterial endophytes isolated each from Reaumuria soongorica (PalL Maxim.) and Peganum harmala L., and three bacterial endophytes each from Artemisia carvifolia (Buch-Ham.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports that, for example, co-evolution occurs between salt-tolerant plants and endophytes. Host plants can provide suitable habitat and abundant nutrients for endophytes, while endophytes can promote host plant growth by fixing nitrogen releasing auxin and other secondary metabolites [4].…”
Section: Introductionmentioning
confidence: 99%